Resíduos sólidos gerados em um hotel: estratégias de redução do montante a ser destinado ao aterro sanitário - Quaresma, Igor do Nascimento (2020)
The National Policy for Solid Waste (PNRS) classifies such items according to their origin into eleven categories and among them there are those originated from commercial establishments. Among commercial establishments there are the hotels, composing the tourism industry, a sector in a steady development, contributing for the world gross product. The hotels ares are recognised as large waste generators. The aim of this research was to analyse the reduction of the amount of solid waste generated in a hotel, to be disposed of in a sanitary landfill, resulting from the following measures: selective collection, composting and vermicomposting. The characterisation and quantification of the solid waste generated by the hotel was carried out, which enabled the calculation of its per capita generation rate and the application of minimising strategies. The results showed that during seven months, the hotel generated approximately 227.62 kg/day of solid waste, with a per capita generation rate of 1.343 kg/person.day. The generated waste was constituted by organic waste (76.12%), refuse (14.89%) and dry recyclable waste (9.05%). Therefore, the hotel in consideration shows a potential of 85% for waste recycling, via selective collection and composting and/or vermicomposting. The selective collection for the recycling of dry waste was capable of giving destination to 100% of the generated waste to the waste pickers' co-operative, at a rate of 20.60 kg/day. This result is in compliance with the National Policy of Solid Waste, by destining the solid waste generated in the business in an environmentally adequate way. The vermicomposting unit managed to give an environmentally adequate destination to up to 2.2% of the organic waste which was generated in the establishment, at a rate of 3.44 kg/day. The decentralised composting was capable of giving destination 17.15% of the organic waste generated by the hotel in an environmentally adequate way, at a rate of 33.31 kg/day. Therefore, with the adoption of these strategies of minimisation, the hotel could avoid sending up to 19.35% of its organic waste to the sanitary landfill of the city of João Pessoa. Therefore, the minimisation strategies managed to give environmentally adequate destination to the organic waste which was generated in the hotel, complying with the National Policy of Solid Waste. The strategies applied here can have a positive impact in the reduction of solid waste which is disposed of in the sanitary landfill of the city of João Pessoa, as the per capita generation rate could be reduced by more than 85%, dropping from 1.343 to 0.199 kg/person.day in case the totality of the organic waste is processed through composting and/or vermicomposting.